Perceptions of forested watershed protection initiatives in highland tourism area: the case of Cameron Highlands - Empidi, Arlixcya Vinnisa; Emang, Diana (Faculty of Agriculture and Food Sciences, Universiti Putra Malaysia Bintulu Sarawak Campus, 2019)
The theory of planned behaviour (TPB) is applied in the context of forested watershed protection initiatives in highland tourism area of Cameron Highlands. Public’ perceptions on protection initiatives, i.e the management of fertilisers and pesticides in agricultural activity, voluntarily engagement in combating forest encroachment, and participating in conservation campaign are investigated using the face-to-face interview with respondents from five regions in Cameron Highlands (n = 143). The protection initiatives for forested watershed are predicted from the basis of (i) attitude, (ii) subjective norm, and (iii) perceived behavioural control. The effects of demographic characteristics and publics’ perception on protection encroached forested watershed area are also analysed. TPB comprises of measurement for the direct effects, where the subjective norms is found to have significant explanatory factor when analysed using Pearson correlation models. Other measurements including, the attitude and control factors have smaller but mutually equal effects on the respondents’ intention to protect the forested watershed area after being encroached from intensive agriculture and other farming activities. Considering both direct and indirect effects via attitude, subjective norms, and perceived behavioural control, the influence of government is perceived stronger in encouraging public to be involved in sustainable agriculture –oriented programme, in order to protect forested watershed in Cameron Highlands. Meanwhile, the engagement in awareness campaign regarding the management of fertilisers and pesticides in agricultural activity is also perceived important though seen as the only minor part of the initiatives. The findings show that the policy makers should implemented the protection initiatives based on the publics’ attitude, subjective norms, and perceived behavioural control. This is especially vital to conserve and protect the aesthetic of Cameron Highlands as a favourable highland tourism destination.